2019
DOI: 10.1002/cssc.201900833
|View full text |Cite
|
Sign up to set email alerts
|

Continuous‐Flow Oxidation of HMF to FDCA by Resin‐Supported Platinum Catalysts in Neat Water

Abstract: The oxidation reaction of 5‐hydroxymethylfurfural to the bioplastic monomer 2,5‐furandicarboxylic acid over heterogenous resin‐supported Pt catalysts was investigated in detail, under continuous flow, base‐free conditions, and in neat water. The product was continuously obtained in 99 % yield by running the reaction at 120 °C, 303 s residence time, 1.2 mL min−1 O2 flow rate, and 7.7 bar O2 pressure. The product was isolated with a high space‐time‐yield of 46.0 g L−1 h−1 without purifications or acid/base treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 48 publications
1
49
0
Order By: Relevance
“…Pt on resin‐support (Pt@Dowex‐Na) was explored in continuous‐flow regime by Liguori et al. in a home‐made continuous‐flow reactor, which was designed to allow for concurrent flows of substrate solution and oxygen gas (up to 64 bar pressure and 40 mL min −1 ) through the reactor housing the heterogeneous catalyst [95] . The solid catalyst was packed into a commercial Omnifit Labware Glass Column (3.0 mm i.d.×50 mm length, 353 μL volume) resistant up to 1200 psi and equipped with 5.0 μm frits at the entrance of the catalyst bed to ensure an optimum flow distribution.…”
Section: Oxidation Of Hmf Via Innovative Protocolsmentioning
confidence: 99%
“…Pt on resin‐support (Pt@Dowex‐Na) was explored in continuous‐flow regime by Liguori et al. in a home‐made continuous‐flow reactor, which was designed to allow for concurrent flows of substrate solution and oxygen gas (up to 64 bar pressure and 40 mL min −1 ) through the reactor housing the heterogeneous catalyst [95] . The solid catalyst was packed into a commercial Omnifit Labware Glass Column (3.0 mm i.d.×50 mm length, 353 μL volume) resistant up to 1200 psi and equipped with 5.0 μm frits at the entrance of the catalyst bed to ensure an optimum flow distribution.…”
Section: Oxidation Of Hmf Via Innovative Protocolsmentioning
confidence: 99%
“…As a result, during the two-week neutral continuousflow reaction, the aerial oxidation over 5% Pt/ZrO 2 catalysts steadily afforded full HMF conversion with FDCA yield of up to 98% at 100°C with a 0.5 wt% HMF feed (liquid hourly space velocity = 3 h À1 ), in spite of inhibition occurring by precipitate. Recently, Liguori et al [125] exploited a continuous-flow production of FDCA in neat water using Pt nanoparticles immobilized on sulfonated DOWEX 50WX2-100 cation-exchange resin (Pt@Dowex-Na) as a https://engine.scichina.com/doi/10.1016/j.jechem.2020.05.068 catalyst, realizing productivity of 1.74 mmol g cat -1 h À1 in 99% yield at 120°C and 0.77 MPa O 2 with 303 s residence time. The home-made continuous-flow system, composing mainly of a catalyst loaded glass tube reactor (I.D = 3 mm, L = 50 mm) and a controlled feeding apparatus, could afford a space-time-yield of 46 g FDCA L À1 h À1 in 99% purity after water withdrawal (Fig.…”
Section: Base-free Systemmentioning
confidence: 99%
“…It was suggested that under certain circumstances, PET may leach phthalates [164], which are known for potentially adverse health effects and subject to ECHA regulation restrictions [165,166]. Coupled with the fact that TPA is produced from petrochemical sources, bioderived 2,5-furandicarboxylic acid has been proposed as TPA replacement in the production of plastic bottles, representing one of the rare examples of industrial manufacture of biobased polymers [167,168].…”
Section: Petmentioning
confidence: 99%